Gendering merit: How the discourse of merit in diversity disclosures supports the gendered status quo on Canadian corporate boards. (March 2021) - Ben-Amar, Walid; Bujaki, Merridee; McConomy, Bruce; McIlkenny, Philip
Highlights: Gender diversity disclosures of Canadian public companies are analyzed. "Merit" and "diversity" are socially constructed to largely exclude women. Many companies focus on "merit" to justify having fewer women directors. Disclosures of companies referring to merit are less readable. Patriarchal structures are revealed in the language of diversity disclosures. Abstract: The diversity disclosures by Canadian corporations are examined to show how references to 'merit' and 'diversity' are used strategically by many corporations to support the gendered status quo and to resist pressures to increase the representation of women on boards. References to 'merit' and 'diversity' in the first mandatory corporate governance diversity disclosures of a sample of corporations from the Toronto Stock Exchange are analyzed using critical discourse analysis to assess the extent to which these disclosures are used to legitimize current board recruitment practices and to maintain the gendered status quo. We find that corporations referring to merit in their disclosures tend to have fewer women directors than corporations that do not mention merit. In addition, we assess the readability of the disclosures. We find that those referring to merit tend to be less readable, suggesting efforts to obfuscate. This research highlights the patriarchal power structures underlying corporate board appointments and shows how these power relationships are revealed in the language corporations choose to use in their diversity disclosures. 'Gender', 'diversity' and 'merit' are socially constructed concepts. Until the gendered roots of the language of merit-based policies are acknowledged, corporations have little incentive to challenge the status quo and engage substantively with diversity. Overcoming corporate resistance to change may require a range of innovative practices by corporations and regulators, up to, and possibly including, mandating levels of women's representation on corporate boards.